Hot Water Rocket System (HWRS) - preliminary design and prototype development of a pressurized how water casing (PHWC) - Kashif, Syed Muhammad (s.n, 2012)
The project fund was successfully used in design and indigenous development of a lab scale Hot Water Rocket System (HWRS). Among the important accomplishments were the design and development of a pressurized water container. Furthermore, a metallic nozzle was manufactured in addition to the procurement of heating mechanism and allied electronic subsystems for performance monitoring and control.